2016
DOI: 10.1155/2016/1694265
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Mesh Application during Colostomy to Prevent Parastomal Hernia: A Meta-Analysis

Abstract: Background. Parastomal hernia is a common complication after stoma formation, especially in permanent colostomy. The present meta-analysis aimed to evaluate the effectiveness of prophylactic mesh application during permanent colostomy for preventing parastomal hernia. Methods. Randomized controlled trials comparing outcomes in patients who underwent colostomy with or without prophylactic mesh application were identified from PubMed, EMBASE, Science Citation Index, and the Cochrane Libraries. Results. This meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
0
10
0
3
Order By: Relevance
“…In the case of open surgery, the mesh is implanted preperitoneally, and in the case of laparoscopy, intraperitoneal implantation is preferred [ 13 , 32 , 57 ]. Meta-analyses of randomised studied performed until the end of 2016 with the aim of assessing the effectiveness of prophylactic prosthetic implantation during stoma construction revealed that the prophylactic approach can potentially significantly reduce the risk of parastomal hernia and does not entail complications related to the presence of the mesh itself [ 59 , 60 ]. However, the authors of one of the mentioned meta-analyses emphasized that before any conclusions are reached, one must account for the fact that the studies analysed varied considerably in terms of the employed methods and the type of stoma constructed, and that the studied patient populations were relatively small and observed over relatively short periods of time [ 60 ].…”
Section: Surgical Prophylaxismentioning
confidence: 99%
“…In the case of open surgery, the mesh is implanted preperitoneally, and in the case of laparoscopy, intraperitoneal implantation is preferred [ 13 , 32 , 57 ]. Meta-analyses of randomised studied performed until the end of 2016 with the aim of assessing the effectiveness of prophylactic prosthetic implantation during stoma construction revealed that the prophylactic approach can potentially significantly reduce the risk of parastomal hernia and does not entail complications related to the presence of the mesh itself [ 59 , 60 ]. However, the authors of one of the mentioned meta-analyses emphasized that before any conclusions are reached, one must account for the fact that the studies analysed varied considerably in terms of the employed methods and the type of stoma constructed, and that the studied patient populations were relatively small and observed over relatively short periods of time [ 60 ].…”
Section: Surgical Prophylaxismentioning
confidence: 99%
“…Mesh reinforcement as prophylaxis at initial stoma creation has also been shown to have a lower incidence of PSH requiring surgical repair (2.3 vs. 8.4%; p = 0.005) than that of a control group [33]. However, these four recent meta-analyses demonstrated no signiicant increases in stoma-related complications such as parastomal infection [33,42,43], wound infection [43], stomal prolapse [33], stricture [33], necrosis [42,43], and stenosis [43].…”
Section: Preventionmentioning
confidence: 99%
“…In view of these encouraging preliminary results, an increasing number of clinical studies have documented the safety and efectiveness of prophylactic placement of mesh. Very recently, four meta-analyses ( Table 5) have shown that prophylactic mesh application at the time of stoma creation is a promising method and may reduce the incidence of PSH, without an increased risk of mesh-related peristomal complications [33,[41][42][43]. These results have been evident when obtained using either clinical (6.5-10.8 vs. 28.8-32.4%) or radiological (34 vs. 55%) outcome measures [33,43].…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve systematic reviews and meta-analyses have now been published regarding the use of prophylactic mesh during primary stoma creation [28][29][30][31][32][33][34][35][36][37][38][39]. All reviews have demonstrated a statistically significant risk reduction of PSH with the use of prophylactic mesh.…”
Section: Quality Of Evidence Low Strength Of Recommendation Nonementioning
confidence: 99%